2018
DOI: 10.1007/s10265-018-1049-2
|View full text |Cite
|
Sign up to set email alerts
|

Low assimilation efficiency of photorespiratory ammonia in conifer leaves

Abstract: Glutamine synthetase (GS) localized in the chloroplasts, GS2, is a key enzyme in the assimilation of ammonia (NH) produced from the photorespiration pathway in angiosperms, but it is absent from some coniferous species belonging to Pinaceae such as Pinus. We examined whether the absence of GS2 is common in conifers (Pinidae) and also addressed the question of whether assimilation efficiency of photorespiratory NH differs between conifers that may potentially lack GS2 and angiosperms. Search of the expressed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
2
12
3
Order By: Relevance
“…The present study suggested that the differences in the subcellular localizations of CAT and GLO yielded a bypass from Ser to glycolate via the oxidative decarboxylation of OH-Pyr in conifer photorespiration. Together with the previous finding of an absence of GS2 in conifer leaves (Cánovas et al, 2007; Miyazawa et al, 2018), the present study supported the contention that conifer gymnosperms have a different photorespiratory mechanism compared with angiosperm C3 species. It is known that H 2 O 2 decarboxylates not only OH-Pyr, but also glyoxylate, which is then converted to formate (Walton and Butt, 1981).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study suggested that the differences in the subcellular localizations of CAT and GLO yielded a bypass from Ser to glycolate via the oxidative decarboxylation of OH-Pyr in conifer photorespiration. Together with the previous finding of an absence of GS2 in conifer leaves (Cánovas et al, 2007; Miyazawa et al, 2018), the present study supported the contention that conifer gymnosperms have a different photorespiratory mechanism compared with angiosperm C3 species. It is known that H 2 O 2 decarboxylates not only OH-Pyr, but also glyoxylate, which is then converted to formate (Walton and Butt, 1981).…”
Section: Discussionsupporting
confidence: 91%
“…GS2 assimilates the ammonia (NH 3 ) that is produced during the Gly-to-Ser conversion mediated by glycine decarboxylase complex (GDC) reactions in mitochondria. Conversely, GS2 is absent from the leaves of conifers, and it is considered that one of the cytosolic types of GS could be a substitute (Suárez et al, 2002; Cánovas et al, 2007; Miyazawa et al, 2018). The leaves of conifers such as Cryptomeria japonica and Pinus densiflora exhibited higher NH 3 emission potentials than did angiosperm leaves, indicating a lowered NH3 assimilation rate during photorespiration in conifers (Miyazawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, GSIIe can be used as a good phylogenetic marker in seed plants, since the presence or absence of the different GS gene groups is characteristic of the main taxa. Surprisingly, searches for GS sequences in the NGS data from public databases allowed to identify genes encoding GS2 in Cycadopsida species, contrary to previous findings (Miyazawa et al 2018).…”
Section: Discussioncontrasting
confidence: 88%
“…The light dependence and organ gene expression of GS1a and GS2 in P. pinaster (Figure 3), G. biloba (Figure 4) and M. grandiflora (Figure 5) strengthened the previous hypothesis that GS1a fulfills the function of GS2 (Cantón et al 1999;Ávila et al 2001;Gómez-Maldonado et al 2004). Interestingly, one of the two Cys residues involved in the redox modulation of GS2 activity (e.g., C306 in Arabidopsis) was conserved in all the GS1a proteins (Cantón et al, 1993;Choi et al 1999;Miyazawa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As arginine plays an important role in pine as a transient N storage metabolite, the operability of such a mechanism for the rapid interconversion of arginine to ornithine would facilitate a rapid N storage and mobilization. However, no plastidic GS isoform is present in pines and other conifers [ 41 , 42 ], and, therefore, arginine dissimilatory activities would be present in the cytosol in these plants where it will possibly contribute to the cytosolic pool of ornithine. In addition, ornithine is synthesized in the cytosol of plant cells by the action of N-acetyl ornithine deacetylase (NAOD) and serves as a precursor for the biosynthesis of polyamines and alkaloids in this subcellular compartment [ 4 , 43 ].…”
Section: Discussionmentioning
confidence: 99%